Load frequency controller design for Iraqi National Super Grid System using Fuzzy logic controller - Mohamed, H.A.F.; Hassan, L.H.; Moghavvemi, M.; Yang, S.S. (2008)
This paper presents a Fuzzy Gains Scheduled Proportional and Integral (FGPI) controller for Load Frequency Control (LFC) of the Iraqi National Super Grid system (INSGS). A linear-time-invariant mathematical model is derived for the system that consists of six generating stations with various types of turbines. Maintaining frequency of each area and the net tie-line power at scheduled value due to the load perturbations are considered in this study. Simulation of the proposed control scheme show better results and transient performance improvements when compared to the conventional method which is also simulated in this paper.